HEART FAILURE WITH PRESERVED EJECTION FRACTION: THE CENTRAL ROLE OF LIFESTYLE MODIFICATION AND NONPHARMACOLOGICAL THERAPIES - Anna-Maria Grzeczka; Katarzyna Pinkowska; Weronika Nawrocka; Zuzanna Korbel; Zuzanna Taciak; Mikołaj Jaszowski; Inez Michalska; Agnieszka Dąbrowska; Patrycja Pietraszkiewicz; Paula Żak; Filip Glista (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Heart failure with preserved ejection fraction (HFpEF) is a condition characterized by significant morbidity and mortality, as well as a considerable burden on healthcare systems. Until recently, sodium-glucose co-transporter 2 (SGLT2) inhibitors were the only drug class to demonstrate a consistent benefit in clinical outcomes among these patients. HFpEF is a complex, multifactorial disorder frequently associated with advanced age, obesity, hypertension, diabetes, and sedentary lifestyle. Many of these risk factors are potentially modifiable.Aim of the Study: The aim of this article is to provide a comprehensive overview of the role of nonpharmacological interventions and lifestyle modifications in the management of HFpEF, emphasizing current evidence for their effectiveness and highlighting the importance of patient-centered, multidisciplinary approaches in improving clinical outcomes.Materials and Methods: A thorough review of the literature was conducted using the PubMed database, Google Scholar with search terms including “heart failure with preserved ejection fraction”, “HFpEF treatment”, “lifestyle modification”, “obesity”, “diet”, “exercise”, vagus nerve stimulation” and related keywords.Results and Conclusions: Nonpharmacological interventions, including exercise training, dietary modification, weight management, and patient education, have demonstrated significant benefits in improving functional capacity, quality of life, and cardiovascular risk profiles in patients with HFpEF. Although pharmacological treatment options remain limited, lifestyle-based strategies are essential components of comprehensive care for this population. Future research should continue to refine and personalize nonpharmacological approaches to further improve outcomes for individuals living with HFpEF.